La vulnerabilidad del embarazo en las trabajadoras del sexo - Maggi, Mayara Lorenzo; dos Santos, Gustavo Gonçalves [UNESP]; Cabral, Francisco Romero (Sociedad de Obstetricia y Ginecologia de Venezuela, 2021)
Objective: To evaluate the exposure of the mother-baby binomial to complications in sex workers. Methods: This is an integrative literature review that followed a 6-phase system. The research took place in the Virtual Health Library in the following databases: Nursing Database (BDENF- Nursing), Online Medical Literature Analysis and Recovery System (Medline), Latin American Literature of Health Sciences (LiLACS), Spanish Bibliographic Index of Health Sciences (IBECS-ES), National Center for Biotechnological Information (NCBI), SAGE Journals with the descriptors: sex workers and sexually transmitted infections, prostitution and sexually transmitted infections, prostitution and vulnerability, from March to April 2019; 105 articles were identified and were submitted to the exclusion and inclusion criteria, and 25 publications were obtained for the sample. Results: Based on the analysis of the articles the following categories were determined: sexually transmitted infections (STIs), violence and illicit or licit drugs are linked. Conclusion: Despite the limitation of sampling, the study allowed us to evaluate that the mother-baby binomial is vulnerable to several complications such as spontaneous abortion, growth restriction, premature labor, fetal and/or maternal death, prematurity, physical and behavioral abnormalities of mother and baby, and placental detachment, due to suffered violence, acquired sexually transmitted infections and used substances.
The vulnerability of pregnancy in sex workers
Keywords: Pregnancy; Sex workers; Vulnerability